MEASURING LANGUAGE ANXIETY OF EFL STUDENTS IN PUBLIC SPEAKING - Rizka Indahyanti; Ali Wira Rahman; Muthmainnah Mursidin (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
Research on speaking anxiety has often been the focus of research in language learning to date. This research topic is important to provide information about the level of anxiety they experience when speaking English and to what extent it impacts the quality of students' speaking. Therefore, implementing research is important for developing strategies for learning English according to the habits and challenges they experience. This study examines students' anxiety levels, especially during public speaking. Data was collected using the Public Speaking Class Anxiety Scale (PSCAS) questionnaire and then analyzed separately based on anxiety, communication apprehension, comfort in speaking English, and fear of negative evaluation. The results showed that 50% of students were at the medium level, 35% at the high level, and 15% at the low anxiety level. Anxiety arises from internal factors such as a tense and stiff body, a heart beating faster, and the inability to control body movements. External factors such as fear of being laughed at and getting a negative response from the public also cause anxiety. This study also found that the main causes of anxiety are lack of grammar knowledge, lack of vocabulary mastery, and failure to construct good sentences